2016
DOI: 10.1017/s1368980016003074
|View full text |Cite
|
Sign up to set email alerts
|

Choice architecture to promote fruit and vegetable purchases by families participating in the Special Supplemental Program for Women, Infants, and Children (WIC): randomized corner store pilot study

Abstract: Objective Conduct a pilot study to determine if improving the visibility and quality of fresh produce (choice architecture) in corner stores would increase fruit/vegetable purchases by families participating in the Special Supplemental Nutrition Program for Women, Infants and Children (WIC). Design Six stores were randomly assigned to choice architecture intervention or control. Store-level WIC sales data were provided by the state. Primary outcomes were WIC fruit/vegetable voucher and non-fruit/vegetable vo… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
2
1

Citation Types

1
95
0

Year Published

2017
2017
2023
2023

Publication Types

Select...
9

Relationship

1
8

Authors

Journals

citations
Cited by 59 publications
(96 citation statements)
references
References 47 publications
1
95
0
Order By: Relevance
“…The latter used a fake food buffet, 13 a Foodscape Laboratory 26 and an online shelf-display. 27 In the field studies, different settings were involved, including dining facilities or cafeterias in schools (11), cafeterias in hospitals (2) as well as restaurants, buffet lines at conferences (2; 28,29 ), a cafeteria at a workplace, 30 a university, 31 a train station, 32 corner stores 33 and a swimming pool. 34 Most studies used a within subjects pre-post interventions design (10), or a between subjects design with a control and treatment group (9), while a minority used both a between-and within subjects design (4).…”
Section: Narrative Synthesismentioning
confidence: 99%
“…The latter used a fake food buffet, 13 a Foodscape Laboratory 26 and an online shelf-display. 27 In the field studies, different settings were involved, including dining facilities or cafeterias in schools (11), cafeterias in hospitals (2) as well as restaurants, buffet lines at conferences (2; 28,29 ), a cafeteria at a workplace, 30 a university, 31 a train station, 32 corner stores 33 and a swimming pool. 34 Most studies used a within subjects pre-post interventions design (10), or a between subjects design with a control and treatment group (9), while a minority used both a between-and within subjects design (4).…”
Section: Narrative Synthesismentioning
confidence: 99%
“…Other farmers' market studies analyse self-reported use of government incentive programs, government incentive sales data or records of coupon redemption [61][62][63][64][65][66], self-reported amounts spent [67] or total sales [39]. Some studies on convenience stores use purchase data collected using these same methods [68][69][70][71][72][73][74][75]. Given technological advances and changing legal requirements [76] in tracking sales, point of sales (POS) terminals are starting to gain popularity in UPS.…”
Section: Introductionmentioning
confidence: 99%
“…Another study reported observing changes in POP signs at mid-intervention and post-intervention [28]. However, unlike other intervention studies, El Valor was not successful in capturing changes in other aspects of the marketing mix elements such as the availability of fresh, canned, and frozen FVs, shelf space dedicated to fresh FVs, and fresh FV displays [11,21,23,24,26,[53][54][55]. For example, two previous in-store interventions reported successful increases in the availability of fresh and/or canned FVs [53,56], while another study reported success in replacing shelf space dedicated to snack foods with shelf space dedicated to FVs [11].…”
Section: Discussionmentioning
confidence: 99%